Extraction association rules from the biochemistry parameters for diagnosing hyperthyroidi - Dogan, Sengul; Turkoglu, Ibrahim (My University, 2008)
In this study a decision support system has been projected from the biochemistry blood parameters which will be very helpful and will make everything easier for the physicians in the diagnosis of Hyperthyroidi. The system operation is achieved via the association rules structure which is related as one of the data mining techniques. The basic characteristic of the thyroid hormone parameters that is, TSH, FT3, FT4, TT3 and TT4 parameters are used in the process of entering the system and finally Hyper(%) results have been evaluated at the end of this process. Data of 472 patients are evaluated in the projected system. The results of the decision support system have completely matched with those of the physicians' decisions. ©2008 IEEE.
Hi?perti?roi?di? teşhi?si? i?çi?n bi?yoki?mya parametleri?nden bi?rli?kteli?k kurallari çikarimi
2008 IEEE 16th Signal Processing, Communication and Applications Conference, SIU -- 20 April 2008 through 22 April 2008 -- Aydin -- 74111
Keywords: Administrative data processing; Artificial intelligence; Association rules; Associative processing; Biochemistry; Data mining; Decision making; Decision theory; Information management; Management information systems; Signal processing; Basic characteristics; Blood parameters; Data mining techniques; Decision supports; Projected systems; System operations; Thyroid hormones; Decision support systems